The Relationship between Service Quality Dimensions and Customer Satisfaction towards Hypermarket in Malaysia - Ogiemwonyi, Osarodion; Harun, Amran; Rahman, Abdul; Nurul Alam, Mohammad; Majeed Hamawandy, Nawzad (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to measure the relationship between service quality dimensions and customer satisfaction in Malaysian hypermarkets. Data was collected from 160 consumers who patronized hypermarkets in the state of Negeri Sembilan, and a convenience sampling method was applied. The data was then analyzed using Partial Least Squares (PLS) and SmartPLS v.3.0 software to develop hypotheses that include customer satisfaction and all service quality dimensions. SPSS v.20 software was utilized to analyze respondents’ demographic data. Findings show that four service quality dimensions were empirically significant except for assurance. Reliability was found to have the highest impact on customer satisfaction, followed by tangibility. This study suggests that retail service providers need to recognize the significance of service quality to build a positive image for hypermarket distribution chains.